Post-Discharge Cardiovascular Complications in Noncardiac Surgery: Incidence and Prediction - D. A. Sokolov; I. A. Kozlov (Общая реаниматология)
The aim of this study was to assess the incidence of cardiovascular complications (CVC) within 12 months after vascular surgery and to analyze inpatient perioperative examination data to identify potential predictors.   Materials and Methods. A prospective cohort study included 103 patients aged 66 years [61–70] who underwent vascular surgery. Clinical outcomes within 12 months after surgery, including CVC and/or other cardiac events (composite outcome) and cardiac death, were assessed by telephone interviews with patients or their relatives. Patient physiological parameters, comorbidities, cardiac risk indices (CRI), platelet-lymphocyte ratio (PLR), concentration of N-terminal pro-B-type natriuretic peptide (NT-proBNP), and other parameters were obtained and analyzed from medical records. Logistic regression and ROC analysis were used to assess the predictive power of the investigated indicators.   Results. The composite outcome was recorded in 33 % of cases and cardiac death occurred in 6.8 %. The risk of the composite outcome was associated with ASA class (OR 2.7413; 95 % CI 1.1126–6.7541), whereas the risk of perioperative myocardial infarction or cardiac arrest was associated with CRI (OR 1. 6051; 95 % CI 0.6645–2.0215), American University of Beirut (AUB) CRI (OR 2.1106; 95 % CI 1.0260–4.3414), PLR (1.0120; 95 % CI 1.0018–1.0222), and NT-proBNP concentration during hospitalization. Concurrent congestive heart failure (OR 5.0658; 95 % CI 1.2400–20.6956), revised CRI (OR 2.1024; 95 % CI 1.0572–4.1813), Khoronenko CRI (OR 103.76; 95 % CI 1.8752–5796.55), AUB CRI (OR 3.1902; 95 % CI 1.1040–9.2181), and NT-proBNP concentration all increased the risk of cardiac death. Predischarge NT-proBNP levels < 179 pg/mL (OR 1.0071; 95 % CI 1.0038–1.0104; AUC 0.795) and maximum postoperative NT-proBNP levels were reliable predictors of the composite outcome. The most effective predictor of postoperative mortality was a maximum NT-proBNP concentration > 303 pg/mL after surgery (OR 1.0039; 95 % CI 1.0015–1.0063; AUC 0.836).   Conclusion. CVC developed in 33 % of patients within 12 months after vascular surgery, with cardiac death occurring in 6.8 % of cases. An NT-proBNP concentration > 179 pg/mL before hospital discharge or a maximum NT-proBNP concentration > 248 pg/mL in the postoperative period predicted CVC within one year. Postoperative NT-proBNP concentration > 303 pg/mL was a strong predictor of one-year cardiac mortality. Other factors associated with the risk of postoperative CVC did not provide an accurate prognosis.